Microalgae Chlamydomonas reinhardtii Cultivication as A Single Cell Protein in Raceway Open Pond Bioreactor: Kultivasi Mikroalga sebagai Produsen Protein Sel Tunggal dalam Bioreaktor Kolam Lintasan Terbuka (RACEWAY OPEN POND BIOREACTOR) - Sumardiyono (Jurnal Kimia dan Rekayasa, 2021)
Research on the cultivation of Chlamydomonas reinhardtii in an open pond bioreactor has been carried out using seawater media. Cultivation using media with a depth of 10, 12 and 14 cm to the bottom of the pond, at a temperature of 30, 40 and 50 ° C. The light source is produced by a tube electric lamp (TL) with a power of 8, 15, 23 Watt. Microalgae growth was observed every 8 hours by measuring the density of the cells using a spectrophotometer. The results showed that the depth of cultivation media, temperature, and light intensity affected the growth rate of C. reinhardtii microalgae. The highest number of C. reinhardtii microalgae cells was obtained at a culture media depth of 12 cm, a temperature of 45 ° C, and a light intensity of 15 watts with a cell number of 1.65 x 108. The fastest growth rate of C. reinhardtii microalgae was obtained at a culture media depth of 12 cm, a temperature of 40 ° C, and a light intensity of 23 watts with a k value of 2.71 x 10-2 cells / hour. The highest protein content was obtained at a culture media depth of 10 cm, a temperature of 45 ° C, and a light intensity of 15 watts with a protein content of 4.444 mg / 100 ml sample. AbstrakTelah dilakukan penelitian kultivasi Chlamydomonas.reinhardtii dalam bioreaktor kolam terbuka (openpond bioreactor) dengan media air laut. Kultivasi dilakukan dalam media dengan kedalaman 10 ,12 dan 14 cm terhadap dasar kolam, pada suhu 30, 40 dan 50°C. Sumber cahaya dihasilkan oleh lampu listrik tabung (TL) dengan daya 8, 15, 23 Watt. Pertumbuhan mikroalga diamati setiap 8 jam dengan mengukur densitas selnya menggunakan spektrofotometer. Hasil penelitian didapatkan kedalaman media kultivasi, temperatur, dan intensitas cahaya berpengaruh terhadap laju pertumbuhan mikroalga C. reinhardtii. Jumlah sel mikroalga C. reinhardtii terbanyak didapatkan pada kedalaman media kultur 12 cm, suhu 45 °C, dan intensitas cahaya 15 watt dengan jumlah sel sebanyak 1,65 x 108. Laju pertumbuhan mikroalga C. reinhardtii tercepat didapatkan pada kedalaman media kultur 12 cm, suhu 40 °C, dan intensitas cahaya 23 watt dengan nilai k sebesar 2,71 x 10-2 sel/jam. Kadar protein tertinggi didapatkan pada kedalaman media kultur 10 cm, temperatur 45 °C, dan intensitas cahaya 15 watt dengan kadar protein sebesar 4,444 mg/100 ml sampel.